Exploring How Exposure to Pop Culture English Movies Enriches Vocabulary - Alfaiz, Muhammad Keivan; Said, Iskhak; Irianti, Leni (Universitas Galuh, 2025)
EFL students frequently face challenges in understanding cultural references, idioms, and slang, which can hinder vocabulary acquisition and overall language comprehension. This issue raises important questions about the accessibility and effectiveness of various language learning tools for learners from diverse linguistic and cultural backgrounds. This study explored the impact of using pop culture English movies for vocabulary acquisition among EFL college students. A qualitative case study method was employed, involving 40 participants, with 10 students from each grade level completing a questionnaire and 10 participating in follow-up interviews. Data were collected through Likert-scale questionnaires to explore students’ perceptions and semi-structured interviews to investigate the strategies for learning vocabulary through movies. The results indicated that students generally found movies valuable for vocabulary acquisition, particularly enhancing their listening skills and contextual understanding. Most students reported increased confidence in using new vocabulary learned through movies. They employed various strategies, including note-taking, subtitles, and engaging in peer discussions. However, challenges such as difficulty understanding cultural references and the fast pace of dialogues were significant obstacles. Despite these, many students preferred learning vocabulary through movies over traditional classroom methods. The study concluded that pop culture English movies can be an effective tool for vocabulary acquisition, provided that students are guided in using appropriate learning strategies. Future research should focus on the long-term impact of movie-based learning on vocabulary retention and the potential benefits of different movie genres for language learning.